Effects of the Genetic Depletion of Polysialyltransferases on the Structure and Connectivity of Interneurons in the Adult Prefrontal Cortex - Curto, Yasmina; Alcaide, Julia; Röckle, Iris; Hildebrandt, Herbert; Nacher, Juan (Frontiers in Neuroanatomy, 2019)
Polysialic acid (polySia) is a complex sugar that in the nervous system appears mainly as a posttranslational modification of the neural cell adhesion molecule (NCAM). PolySia plays important roles during brain development, but also in its plasticity during adulthood. Two polysialyltransferases (polyST), ST8SIA2 and ST8SIA4, are involved in the synthesis and attachment of polySia. Both polyST are relevant for developmental migration of cortical interneurons and their establishment in the prefrontal cortex (PFC). In contrast, only ST8SIA4 appears to be important for the structural plasticity of a subpopulation of cortical interneurons in the adult. Interestingly, ST8SIA2 and NCAM are candidate genes for schizophrenia, a disorder in which interneuronal circuits are altered. However, there is still no data on the effects of polyST depletion on the dendritic structure or the connectivity of cortical interneurons. Here, we studied the contribution of each polyST on these parameters in the medial PFC (mPFC) of polyST knock-out mice with GAD67-GFP-labeled interneurons. Genetic depletion of ST8SIA4, but not ST8SIA2, resulted in a decrease in the complexity of the dendritic arbor of interneurons. In contrast, ablation of either of the two polyST induced a decrease in the density of parvalbumin (PV) expressing perisomatic puncta on pyramidal neurons. Thus, the depletion of each polyST results in similar impairments of not only developmental migration but also efferent synaptic connectivity of interneurons. In contrast, the loss of ST8SIA4 has a unique effect on dendritic structure, hence on afferent connectivity, suggesting differential and independent contributions of each polyST to neuritogenesis and synaptogenesis.